Effectiveness and durability assessment, under extreme environmental conditions, of a superhydrophobic coating applied onto sandstone from Carteia roman archaeological site. (16th January 2023) - Elhaddad, Farid; Luna, Manuel; Gemelli, Giada M.C.; Almoraima Gil, M.L.; Mosquera, Maria J.
Graphical abstract: Highlights: Effective interactions between the products and the sandstone are observed. Incorporation of SiO2 NPs enhances hydrophobic properties. Coating durability coating is tested in monumental outdoor heritage. Treatment effectiveness in lab is consistent with the in situ evaluation. Abstract: Superhydrophobic coatings have been often used to protect stone surfaces against water. The durability of these coatings has been rarely tested for monumental heritage exposed to outdoor conditions. In this work, a highly effective superhydrophobic nanomaterial has been applied in the archaeological site of Carteia, which is located next to the sea and an industrial area. The effectiveness and durability of this nanomaterial have been evaluated in the laboratory and after one year of in situ exposure and compared against two specific commercial products. The results revealed that the product prepared in our laboratory exhibited high consolidant and superhydrophobic effectiveness, high static contact angle and low contact angle hysteresis. After one year, our product effectiveness was maintained due to the uniform coating with 4 mm depth penetration. The consolidant and hydrophobic commercial products presented reduced protection, with cracked coatings and poor penetration into the sandstone structure.